2019
DOI: 10.1038/s41598-018-37373-1
|View full text |Cite
|
Sign up to set email alerts
|

Administration of N-Acyl-Phosphatidylethanolamine Expressing Bacteria to Low Density Lipoprotein Receptor−/− Mice Improves Indices of Cardiometabolic Disease

Abstract: Obesity increases the risk for cardiometabolic diseases. N-acyl phosphatidylethanolamines (NAPEs) are precursors of N-acylethanolamides, which are endogenous lipid satiety factors. Incorporating engineered bacteria expressing NAPEs into the gut microbiota retards development of diet induced obesity in wild-type mice. Because NAPEs can also exert anti-inflammatory effects, we hypothesized that administering NAPE-expressing bacteria to low-density lipoprotein receptor (Ldlr)−/− mice fed a Western diet would impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 71 publications
(79 reference statements)
0
27
0
Order By: Relevance
“…Troseid et al [ 114 ] described the association of TMAO with disease severity and survival of patients with chronic HF; the results showed an elevated plasma level of TMAO in patients ( n = 155) with chronic HF compared with the control group. Approximately 50% of patients with the highest levels of TMAO died or received a heart transplant during 5.2 years of follow-up [ 115 ].…”
Section: Gut Microbiota Of Obesity Associated With Cvdmentioning
confidence: 99%
“…Troseid et al [ 114 ] described the association of TMAO with disease severity and survival of patients with chronic HF; the results showed an elevated plasma level of TMAO in patients ( n = 155) with chronic HF compared with the control group. Approximately 50% of patients with the highest levels of TMAO died or received a heart transplant during 5.2 years of follow-up [ 115 ].…”
Section: Gut Microbiota Of Obesity Associated With Cvdmentioning
confidence: 99%
“…Notably, a growing body of clinical evidence related to the prognostic value of TMAO shows that elevated circulating TMAO levels are associated with the presence of coronary plaque vulnerability and that circulating TMAO can directly contribute to enhanced risk for CVD‐related consequences (Li, et al , ; Qi, et al , ) (Table ). Other gut microbiota‐generated metabolites, such as BAs and butyrate, exhibit atheroprotective effects (Jones, et al , ; Brown and Hazen, ), whereas N ‐acyl phosphatidylethanolamines (NAPEs) have no significant effects on aortic lesion size but can markedly decrease the necrotic core area within atherosclerotic lesions (May‐Zhang, et al , ). These observations suggest the potential involvement of gut microbiota metabolism in the development of atherosclerosis.…”
Section: Interactions Between the Gut Microbiota And Cvdmentioning
confidence: 99%
“…However, another study reported that the Coriobacteriaceae family, which is involved in urolithin B production, is positively associated with total cholesterol and LDL levels and is a potential CVD risk biomarker (Romo‐Vaquero, et al , ). Other molecules, such as indoleamine 2,3‐dioxygenase, serotonin (5‐HT) and NAPEs, are also correlated with gut microbiota changes that alter lipid absorption or lipid metabolism, consequently linking the gut microbiota to cardiometabolic phenotypes (Laurans, et al , ; May‐Zhang, et al , ; Singhal, et al , ). Melatonin improves lipid metabolism, and the potential mechanism is related to gut microbiota reprogramming, especially with respect to Bacteroides‐ and Alistipes‐ mediated acetic acid production (Yin, et al , ).…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…Administration of high NAPEs-producing engineered E. coli Nissle 1917 (pNAPE-EcN) successfully improved the obesity of wild-type mice. Furthermore, administration of pNAPE-EcN ameliorated obesity and atherosclerosis lesion necrosis in a mice model of atherosclerosis ( May-Zhang et al, 2019 ). These results demonstrate the potential of engineered microbes in treating metabolic diseases.…”
Section: Microbiome and Metabolic Diseasesmentioning
confidence: 99%